Thermal Performance of Membrane Distillation - Criscuoli, Alessandra (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Membrane Distillation (MD) is based on the evaporation of a hot feed through a microporous and hydrophobic membrane. Thermal energy is needed to heat the feed up to the desired temperature during the process. Therefore, improvements of the thermal performance of MD are important to apply this technology at large scale. The Special Issue "Thermal Performance of Membrane Distillation" focuses on the recent research efforts made in this direction, covering both the development of new membranes and the optimization of the process.​​